Historical evolution of aesthetic dentistry as a science and practice - Muxtorova, Shirinbonu Toxirovna; Majidov, Sherzod Farxodovich (Science and Education, 2024)
The paper studies aesthetic dentistry as an independent field with its own history of development, theoretical basis, also presents the stages of development of aesthetic dentistry in historical aspect, describes odontological parameters, history of teeth whitening, qualitative characteristics of tooth color, stages of development of filling materials, aesthetic constructions.